2000
DOI: 10.1007/s004120000074
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analyses and phylogenetic studies in the Nicotiana section Tomentosae

Abstract: Phylogenetic schemes based on changing DNA sequence have made a major impact on our understanding of evolutionary relationships and significantly built on knowledge gained by morphological and anatomical studies. Here we present another approach to phylogeny, using fluorescent in situ hybridisation. The phylogenetic scheme presented is likely to be robust since it is derived from the chromosomal distribution of ten repetitive sequences with different functions and evolutionary constraints [GRS, HRS60, NTRS, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
196
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(208 citation statements)
references
References 37 publications
12
196
0
Order By: Relevance
“…N. rustica has the sum of the loci observed in these putative parents ( Figure 1c). GISH can be used to distinguish the genomic origin of the chromosomes in allopolyploids (Heslop-Harrison, 1992;Gill and Friebe, 1998) and has been used to confirm the ancestry of allopolyploids in a number of species including tobacco (Parokonny and Kenton, 1995;Lim et al, 2000a). Figure 1d shows that the method distinguishes between chromosomes inherited from progenitors of N. undulata and N. paniculata, the U-and P-genomes of N. rustica respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…N. rustica has the sum of the loci observed in these putative parents ( Figure 1c). GISH can be used to distinguish the genomic origin of the chromosomes in allopolyploids (Heslop-Harrison, 1992;Gill and Friebe, 1998) and has been used to confirm the ancestry of allopolyploids in a number of species including tobacco (Parokonny and Kenton, 1995;Lim et al, 2000a). Figure 1d shows that the method distinguishes between chromosomes inherited from progenitors of N. undulata and N. paniculata, the U-and P-genomes of N. rustica respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One of the best characterised genetic events associated with allopolyploidy is gene conversion at the 18-5.8-26S nuclear ribosomal DNA (rDNA) loci in Nicotiana tabacum L. (Kovarik et al, 1996;Volkov et al, 1999;Lim et al, 2000a). N. tabacum (tobacco) is an allotetraploid (2n ¼ 4x ¼ 48) that formed within the last 6 million years (Olmstead and Palmer, 1991) between N. sylvestris Speg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of rRNA genes by fluorescent in situ hybridization (FISH) has proved to be a useful tool in studies of plant genome organization, chromosome homeologies, cytotaxonomy and evolution (Jiang and Gill, 1994;Moscone et al, 1999;Lim et al, 2000;Nakamura et al, 2001). Raina and Mukai (1999) applied this approach to a few Arachis species and demonstrated that the number of ribosomal rDNA loci is variable.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotiana tabacum (tobacco) is a 5-6 million year old natural amphidiploid derived from ancestors of N. sylvestris, the maternal S genome donor, and N. tomentosiformis the paternal T genome donor (Goodspeed, 1954;Okamuro and Goldberg, 1985;Parokonny and Kenton, 1995;Lim et al, 2000b). Comparisons of the tobacco genome with the genomes of modern diploid relatives have revealed several contrasting evolutionary patterns.…”
Section: Introductionmentioning
confidence: 99%